Pengendalian Persediaan Bio Solar dan Pertalite Pada SPBU Nelayan 58.611.01 yang Dikelola PT. Gresik Migas - Makhrojim, Lafad; Dzulquarnain, Abi Hanif; Harianto, Prayudi (Jurnal Mahasiswa Manajemen, 2023)
Background - The need for fuel oil is a primary need for fishermen, this is an important role for PT Gresik Migas as the manager of the Gas Station, which is a retail business that is an extension of Pertamina to maintain the availability of fuel oil in the community with good inventory control. Objectives - This study aims to describe the inventory control that has been carried out by the company and compare it with the Economic Order Quantity inventory control method. Design/Methodology/Approach - This research uses a qualitative method with a descriptive approach. The data collection techniques used are unstructured interviews, structured interviews, documentation and focused group discussions. Findings - The results of this study state that the inventory control carried out by PT Gresik Migas is less effective and often occurs overstock and stockout because there are no provisions for the order quantity and order time. Meanwhile, inventory control using the Economic Order Quantity method is considered more effective to avoid overstock and stockout with an order quantity of 16,912 liters for Bio Solar and 6,724 liters for Pertalite, with the time to place an order at the inventory point of 15,000 liters for Bio Solar and 6,000 liters for Pertalite. Research Implications - The findings of this study can be used as a reference if further research faces conditions similar to the findings in this study. Research Limitations - This research has limitations on fuel demand forecasting.